Optical Beam Induced Current and Time Resolved Electro-Luminescence in Vertical Cavity Surface Emitting Lasers During Accelerated Aging - Adam W. Bushmaker; Zachary Lingley; Miles Brodie; Brendan Foran; Yongkun Sin (IEEE Photonics Journal, 2019)
Vertical Cavity Surface Emitting Lasers are characterized under a high magnification optical microscope for reliability during accelerated aging using Optical Beam Induced Current and Electroluminescence imaging and spectroscopy, and also with electrical IV characterization. EL image data is captured with time resolution during device failure, and compared to the OBIC images, yielding insight into failure mechanisms. In particular, sudden, localized, permanent reductions in EL intensity around the outside of the laser oxide aperture are observed during the period of failure, indicating step-wise rather than gradual degradation in laser performance. These failure events are temporally correlated with sudden increases in low-injection junction current. Both OBIC and IV characterization suggest mid-gap defect formation as the cause of the observed failures.